Bahasa Inggris - Setyawan, Heri (Jurnal Adabiyah, 2025)
This study explores Said Nursi’s thoughts on interreligious dialogue as articulated in his monumental work, Risale-i Nur, within the socio-political context of Turkey in the 1920s, a period marked by the transition from the Ottoman Caliphate to the secular Republic. Amid tensions between Western modernization and Islamic tradition, Nursi developed a theological and socio-political thoughts that underscored the necessity of interreligious dialogue for the sake of peace, moral integrity, and mutual progress. In particular, The Words and The Letters, sections within Risale-I Nur, reveal Nursi’s understanding that interreligious dialogue arises from a faith-based commitment to truth, compassion, and justice. Nursi argues that ethical solidarity among the Abrahamic faiths, Islam, Christianity, and Judaism, constitutes a share responsibility before humanity and God. Exploration on interreligious dialogue within historical contexts of Turkey, provides an important contribution to finding a model of interfaith dialogue that resists secularist assumptions and remains profoundly relevant to the pursuit of religious harmony in today’s pluralistic world. الملخص تتناول هذه الورقة البحثية أفكار سعيد النورسي حول الحوار بين الأديان، كما عبّر عنها في عمله الرائد "رسائل النور"، وذلك في السياق الاجتماعي والسياسي لتركيا في عشرينيات القرن الماضي، وهي فترة اتسمت بالانتقال من الخلافة العثمانية إلى الجمهورية العلمانية. في خضمّ التوتر بين التحديث الغربي والتقاليد الإسلامية، طوّر النورسي فكرًا لاهوتيًا واجتماعيًا وسياسيًا أكّد على ضرورة الحوار بين الأديان من أجل السلام والنزاهة الأخلاقية والتقدم المشترك. ويكشف كتابا "الكلمات والحروف"، وهما جزء من "رسائل النور"، عن فهم النورسي بأن الحوار بين الأديان ينبع من التزام إيماني بالحق والرحمة والعدالة. وجادل النورسي بأن التضامن الأخلاقي بين الديانات الإبراهيمية - الإسلام والمسيحية واليهودية - مسؤولية مشتركة أمام البشرية والله. إن استكشاف الحوار بين الأديان في سياق التاريخ التركي يساهم بشكل مهم في إيجاد نموذج للحوار بين الأديان يرفض الافتراضات العلمانية ويظل وثيق الصلة بالسعي إلى تحقيق الانسجام الديني في المجتمع التعددي اليوم. Abstrak Penelitian ini mengkaji pemikiran Said Nursi tentang dialog antaragama sebagaimana disampaikan dalam karya monumentalnya, Risale-i Nur, dalam konteks sosial-politik Turki pada tahun 1920-an, periode yang ditandai oleh transisi dari Kekhalifahan Ottoman ke Republik sekuler. Di tengah ketegangan antara modernisasi Barat dan tradisi Islam, Nursi mengembangkan pemikiran teologis dan sosial-politik yang menggarisbawahi perlunya dialog antaragama demi perdamaian, integritas moral, dan kemajuan bersama. Secara khusus, The Words and The Letters, bagian dalam Risale-i Nur, mengungkapkan pemahaman Nursi bahwa dialog antaragama muncul dari komitmen iman terhadap kebenaran, kasih sayang, dan keadilan. Nursi berpendapat bahwa solidaritas etis di antara agama-agama Abrahamik—Islam, Kristen, dan Yahudi—merupakan tanggung jawab bersama di hadapan manusia dan Tuhan. Eksplorasi dialog antaragama dalam konteks sejarah Turki memberikan kontribusi penting untuk menemukan model dialog antaragama yang menolak asumsi sekuler dan tetap relevan secara mendalam terhadap upaya mencapai kerukunan umat beragama di masyarakat plural sekarang ini.